Analisis Viktimologi Terhadap Body Shaming Di Media Sosial (Studi Kasus Pada Akun Instagram @viavallen) - Usmita , Fakhri; Manora Siregar, Elsa (SISI LAIN REALITA, 2021)
Body shaming is a verbal and nonverbal comment that undoubtedly affects victim”s psychic condition. Body Shaming is a new breed of misrepresentation as a result of misusing negative social networking and can occur in public and public figures. The arrival of the phenomenon body shaming on social media is among the forms of cyberbullying. The study is aimed at figuring out how vicariology analyzed the bdy shaming case that dealth with one public figure on social media of instagram. The methods used in this study are visually criminology, while the subject of the study was chosen was a dangdut singer named via vallen. The results of this study are many of the negative comments via vallen received about his physical forms. Via vallen felt the effects of netizen negative comments. The conclusion of this study, seen from the perspective of victimology, is that body shaming can occur in an unrelated relationship between the perpetrator and the victim. Social media use has been known to incite involvement by others in interacting, either as defenders or abusers. If a victim has little or no response to the incident, the feud tendsto remain calm and undeveloped.